MicroRNA-mRNA Co-sequencing Identifies Transcriptional and Post-transcriptional Regulatory Networks Underlying Muscle Wasting in Cancer Cachexia - Fernandez, Geysson Javier; Ferreira, Juarez Henrique; Vechetti, Ivan José; de Moraes, Leonardo Nazario; Cury, Sarah Santiloni; Freire, Paula Paccielli; Gutiérrez, Jayson; Ferretti, Renato; Dal-Pai-Silva, Maeli; Rogatto, Silvia Regina; Carvalho, Robson Francisco (Frontiers in Genetics, 2020)
Cancer cachexia is a metabolic syndrome with alterations in gene regulatory networks that consequently lead to skeletal muscle wasting. Integrating microRNAs-mRNAs omics profiles offers an opportunity to understand transcriptional and post-transcriptional regulatory networks underlying muscle wasting. Here, we used RNA sequencing to simultaneously integrate and explore microRNAs and mRNAs expression profiles in tibialis anterior (TA) muscles of the Lewis lung carcinoma model of cancer cachexia. We found 1,008 mRNAs and 18 microRNAs differentially expressed in cachectic mice compared with controls. Although our transcriptomic analysis has demonstrated a high heterogeneity on mRNA profiles of cachectic mice, we identified a minimum number of differentially expressed genes that were uniformly regulated across cachectic muscles. This set of uniformly regulated genes is associated with the extracellular matrix (ECM), proteolysis, and inflammatory response. We also used the transcriptomic data to perform enrichment analysis of transcriptional factor binding sites in promoter sequences, which revealed activation of the atrophy-related transcriptional factors NF-κB, Stat3, AP-1, and FoxO. Furthermore, the integration of mRNA and microRNA expression profiles identified post-transcriptional regulation by microRNAs of genes involved in ECM organization, cell migration, transcription factors binding, ion transport, and FoxO signaling pathway. Our integrative analysis of microRNA-mRNA co-profiles comprehensive characterized regulatory relationships of molecular pathways and revealed microRNAs targeting ECM-associated genes in cancer cachexia.